Effect of the surfactant nature on the thermo-stability of surface modified SnO2 nanoparticles - Kawaguti, C. A. [UNESP]; Santilli, Celso Valentim [UNESP]; Puldnelli, S. H. [UNESP] (Elsevier B.V., 2008)
The modification of particle surface properties by the addition of small surfactant molecules in the initial sol is one strategy to minimize the strong tendency to aggregation and coarsening of nanoparticles; prepared from the sol-gel process. In this work. the effect of the nature of the surfactant, Tiron (R) (OH)(2)C6H2(SO3Na)(2) H2O, anionic) or Catechol (R) (C6H4-1,2-(OH)(2), non-ionic) or Maptac (R) (IN(CH3)(3)-(CH2)(3)NHCOC(CH2CH3)]Cl-+(-), cationic), grafted on the SnO2 nanoparticles on the mesoporosity of powders fired at 600 degrees C is presented. SnO2 powders were prepared from an one-pot sol-gel route in which the hydrolysis of SnCl4 center dot 5H(2)O in aqueous solution was carried out in presence of the surfactant. The Fourier transform infrared (FTIR) spectroscopy and gravimetric and differential thermo-analysis (TG/DTA) results show that the thermo-stability of surface grafted SnO2 nanoparticles obeys the following series: Tiron (R) > Catechol (R) > Maptac (R). The N-2 adsorption isotherms results evidence that the mesopores texture (specific surface area, pore volume and average pore size) can be tuned in a controlled way by increasing the amounts of Tiron (R) or Catecholo molecules grafted on the surface of SnO2 nanoparticles. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Porosity; Powders; Colloids; Sol-gels (xerogels); Solution chemistry; Tin oxide